Harbours and landing places on the Balkan coasts of the Byzantine empire (4th to 12th centuries) - Ginalis, Alkiviadis 1981-; Heher, Dominik 1984-; Külzer, Andreas 1962-; Preiser-Kapeller, Johannes 1977-; Simeonov, Grigori (European Harbour Data Repository, 2019)
The European Harbour Data Repository is a series of databases which were compiled in the framework of the DFG-funded Priority Program 1630 "Harbours from the Roman Period to the Middle Ages" (Kalmring/von Carnap-Bornheim 2012; Engel/Kunz/Müller/Werther 2018; http://www.spp-hae- fen.de/en/home/). It is part of the virtual HArbour Research Environment "HARE" (http://haefen. i3mainz.hs-mainz.de/) and catalogues harbours, harbour-related infrastructure, and vessels all over Europe with a chronological focus on the Roman and Medieval Period. Different digital volumes of the data repository have been compiled by several project teams within and without the Priority Program. Therefore, the spatial and chronological focus, as well as the size of the datasets, differ significantly. Furthermore, some of the datasets cover a specific region and period which is representative as possible, whereas other datasets focus on selected sites. We try to minimize data overlap, but in some cases, this was not possible. A cross-disciplinary, cross-period, and cross-border database is a challenge. We hope that our method will have a benefit for the research community. Given the spatial and chronological scale and the diversity of sources, this Data Repository does not aim to be exhaustive – and it is still growing, thus not yet completed. Before using this data collection for further analysis, it is absolutely neces - sary "to verify and restrict content spatially and temporally," as recommended by Roosen and Curtis (2018), since the data is patchy especially on a supra-regional scale. We should add that the topics have to be carefully chosen as well, and the data quality must be kept in mind (see e.g. Cooper / Green 2015; Roosen / Curtis 2018; Wilson 2011)